Upplevelsebaserade fritidsaktiviteter för generation Z : En konceptutveckling för ungas delaktighet i Allhuset, Piteå - Lindberg, Britt-Marie; Sibelius, Malin (2014)
The purpose of the study is to examine adolescents associated to generation Zs needs and desires of leisure in Piteå and then develop a concept for the design of how it can be done. This is due to an expressed need in Piteå Municipality of leisure activities for young people in parts of Allhuset. To create activities that attract generation Z, it is important to understand the generation Zs characteristics and have an understanding of today's experience society. We made use of action research and the learning process in order to identify the problem and talks have been held with three focus groups with participants in the generation Z. A concept for how the design of the activities can be done have been created. Validerat; 20140902 (global_studentproject_submitter)